2020
DOI: 10.1007/s10714-020-02728-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability and horizon formation during dissipative collapse

Abstract: We investigate the role played by density inhomogeneities and dissipation on the final outcome of collapse of a self-gravitating sphere. By imposing a perturbative scheme on the thermodynamical variables and gravitational potentials we track the evolution of the collapse process starting off with an initially static perfect fluid sphere which is shear-free. The collapsing core dissipates energy in the form of a radial heat flux with the exterior spacetime being filled with a superposition of null energy and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Equating the appropriate extrinsic curvature components (20) and (24), yields the second junction condition (A.5) as…”
Section: Matching Of the Two Spacetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Equating the appropriate extrinsic curvature components (20) and (24), yields the second junction condition (A.5) as…”
Section: Matching Of the Two Spacetimesmentioning
confidence: 99%
“…A variety of exact solutions to the Einstein field equations, with a matter distribution that has to be necessarily heat conducting, and the nonlinear boundary condition have been found. Some of the resulting astrophysical models are given in the recent treatments [17][18][19][20][21][22][23][24]. The problem of matching general hypersurfaces and junction conditions, containing timelike, spacelike or null surfaces, was analysed by Mars and Senovilla [25].…”
Section: Introductionmentioning
confidence: 99%
“…Explicit models of radiating stars are necessary to study important astrophysical processes including viscosity, thermal effects, particle production at the stellar surface, dissipative processes and gravitational collapse. Some examples of investigations in these directions are contained in [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The study of radiating stars in the presence of heat dissipation and pressure anisotropy has provided us with a myriad of interesting results regarding stability, causality, thermodynamics and the end-state of collapse. It was shown that the time of formation of the horizon is advanced when the principal stresses are unequal within the stellar fluid [20]. In addition, pressure anisotropy leads to higher core temperatures within the collapsing configuration.…”
Section: Introductionmentioning
confidence: 99%